EFFECTS OF MECHANICAL VIBRATION EXPOSURE IN THE IMPROVEMENT OF THE RATE OF STRENGTH PRODUCTION (Fiep Bulletin - online, 2015)
The effect of mechanical vibrations exposure in the development of muscular strength has been thoroughly studied by numerous scientists. Most of the studies point out the fact that mechanical vibrations cause what is called as “tonic vibration reflex” that helps increasing the muscular strength by influences of the mechanism of medullar reflexes.  The aim of the present study was to check the influence of mechanical vibrations applied in the direction of the torque produced by the muscle in the improvement of rate of strength production, in flexor muscles of the elbow through comparison between a conventional isometric training and an isometric training with vibrations simultaneously added to the execution of the Maximal Voluntary Contraction (MVC).  Nineteen volunteers, all males, at the age of 24  3,28 years, not trained, were divided into two strength training groups. The group 1 was supposed to execute an isometric training and group 2 an isometric training with mechanical vibrations exposure (frequency of 8 Hz and amplitude of 6 mm).  Both groups executed 12 MVC's, duration of 6s each starting from the moment of peak of strength with intervals of 2 minutes between repetitions, 3 times a week during 4 weeks. The results showed that there was no significantly difference (p>0,05) between the group trained with addition of vibrations and the group trained isometrically when comparing improvement in the rate of strength production.  It seems that vibration exposure does not interfere directly at the control of the rate of strength production.
Keywords: vibrations; rate of strength production; strength training.